Reverse T3 in patients with hypothyroidism on different thyroid hormone replacement - Julian B. Wilson; Thanh D. Hoang; Martin L. Lee; Ma’ayan Epstein; Theodore C. Friedman (PLoS ONE, 2025)
Background Reverse T3 (rT3) is a biologically inactive form of T3 (triiodothyronine), a thyroid hormone, that is created by peripheral 5 deiodination of T4 (thyroxine) by type 1 and type 3 deiodinase enzymes (D1 and D3 respectively) and may block T3 binding to the thyroid hormone receptor. Approximately 15% of patients on L-T4 replacement therapy with a normalized thyroid-stimulating hormone (TSH) report experience continued fatigue and other hypothyroid symptoms; therefore, efforts are needed to understand why this occurs and how it can be corrected. Decades ago, endocrinologists realized that in patients with severe illnesses, rT3 is typically high and T3 is typically low; this was termed “euthyroid sick syndrome”. More recently, functional medicine and other doctors, have argued that high rT3 is detrimental and can block T3 from binding to the thyroid hormone receptor. Due to the lack of peer-reviewed publications on this topic, functional medicine doctors continue to rely heavily on rT3 levels to treat patients that may have no other laboratory findings of hypothyroidism and often prescribe L-T3-only preparations to patients in an effort to lower rT3. Methods The initial rT3 measurements done by liquid chromatography/tandem mass spectrometry (LC/MS-MS) were retrospectively analyzed from the initial blood tests in 976 consecutive patients, with symptoms of fatigue and treated for hypothyroidism, in a private Endocrinology practice. TSH, free T3 and free T4 were measured by electrochemiluminescence immunoassay (ECLIA). The upper limit of normal rT3 (24.1 ng/dL) was used as a cut-off for results above the normal range. Results The number of patients with rT3 levels above normal range varied significantly with the type of thyroid hormone replacement prescribed. The highest rate of an elevated rT3 was 20.9% (29/139) in patients taking T4 alone. Nine% (31/345) of patients not taking thyroid hormone replacement had elevated rT3. Patients on all types of L-T4 treatment had higher rT3 levels than those not on L-T4 treatment (p < 0.00001) and they also had a higher percentage of rT3 levels above the cutoff of 24.1 ng/dL (p < 0.00001). Linear regression analysis showed rT3 levels correlated with free T4 and free T3 levels and inversely with log TSH levels. Conclusions This study found elevated rT3 levels in patients with symptoms of fatigue on various thyroid hormone replacements with the highest levels of rT3 in those taking L-T4 replacement alone and the lowest levels of rT3 in those on preparations that contained L-T3 alone.